First-time handling of different inhalers by chronic obstructive lung disease patients. (8th August 2020) - Harb, Hadeer S.; Laz, Nabila Ibrahim; Rabea, Hoda; Abdelrahim, Mohamed E. A.
Abstract: Background: There is a lack of guidance on inhaler device selection and how to individualize inhaler choice when prescribed for the first-time. Aim of the work: To compare different inhalers regarding ease of use and number of counseling attempts needed for correct handling in subjects with a first experience to such inhalers; also, to investigate if there is a correlation between total correct steps achievements and patient demographics/clinical variables. Method: An open-label, non-drug interventional, cross-over study was conducted including 180 Egyptian patients with chronic obstructive pulmonary disease (COPD). The study evaluated handling of the most common inhalers in subjects with a first experience with them before hospital discharge. Subjects were randomized to handle 10 placebo inhalers including: [metered dose inhaler (pMDI), Aerolizer, Handihaler, Turbohaler, Diskus, Breezhaler, Ellipta, Easyhaler, Diskhaler, and Respimat] without receiving verbal or demonstrative instruction with allowable access to the patient information leaflets in native language supported by figures with enough time to read (baseline assessment). Subjects were then crossed-over to other inhalers with a first experience randomly. Inhalers with a reported past-experience were excluded. Inhaler-technique was assessed by using previously defined checklists, including essential steps and critical errors. The whole handling of the inhaler was demonstrated and the number of counseling attempts needed to correct handling was recorded. Patient demographics and clinical variables were recorded and correlated with correct handling steps. Results: The baseline percentages of total correct steps achievements as mean ± SD were 50 ± 19, 52 ± 16, 58 ± 14, 60 ± 17, 64 ± 10, 67 ± 16, 72 ± 17, 73 ± 11, 77 ± 14 and 86 ± 11% for Respimat, pMDI, Diskhaler, Diskus, Aerolizer, Handihaler, Easyhaler, Turbohaler, Breezhaler, and Ellipta respectively with p < 0.001. Baseline percentages of participants with at least 1 critical error significantly differed between inhalers (p < 0.05) with Ellipta showing the lowest percentage (37%). pMDI, Diskhaler, and Respimat showed the highest percentages (100%, 97% and 94% respectively). The number of counseling attempts needed to reach correct handling showed a significant difference among inhalers (p < 0.05). Ellipta showed the highest percentage of participants with correct handling with no counseling (20%) and the highest percentage of participants achieved with one counseling attempt (78%). Diskhaler, pMDI, and Respimat were the only inhalers included in a fourth counseling attempt (15%, 9%, and 6% respectively). Weak and very weak correlations were found between patient demographics/clinical variables and percentages of total correct steps achievements. Conclusion: Inhalers techniques greatly vary in their ease of use (self-explaining) ranging from easy inhalers (Ellipta) to intermediate inhalers (breezhaler, Easyhaler, Turbohaler, Aerolizer, Handihaler, and Diskus) followed by the most difficult inhalers (pMDI, Diskhaler, and Respimat). That must be considered when prescribing inhalers for the first time; choice of the inhaler should, in part, be based on ease of use and to be accompanied by repeated counseling.